1998
DOI: 10.1037/0278-6133.17.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Types of stressors that increase susceptibility to the common cold in healthy adults.

Abstract: Two-hundred seventy-six volunteers completed a life stressor interview and psychological questionnaires and provided blood and urine samples. They were then inoculated with common cold viruses and monitored for the onset of disease. Although severe acute stressful life events (less than 1 month long) were not associated with developing colds, severe chronic stressors (1 month or longer) were associated with a substantial increase in risk of disease. This relation was attributable primarily to under-or unemploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
304
5
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 424 publications
(332 citation statements)
references
References 30 publications
(67 reference statements)
14
304
5
9
Order By: Relevance
“…A series of studies have shown that chronic stress is associated with increased susceptibility to developing a common cold among persons experimentally exposed to an upper respiratory virus (e.g., refs. [14][15][16][17]. This association has been replicated in cross-sectional and prospective studies conducted in natural settings (18).…”
mentioning
confidence: 56%
“…A series of studies have shown that chronic stress is associated with increased susceptibility to developing a common cold among persons experimentally exposed to an upper respiratory virus (e.g., refs. [14][15][16][17]. This association has been replicated in cross-sectional and prospective studies conducted in natural settings (18).…”
mentioning
confidence: 56%
“…Negative life events-Intuitively, it might not seem reasonable to expect symptoms of mania, such as euphoria, elevated self-esteem, and increased productivity, to follow negative life events. It is worth considering, though, that severe stressors have been found to promote a broad array of psychiatric and physical outcomes, including episodes of schizophrenia (Day, 1989), common colds (Cohen et al, 1998), and ulcers (Gilligan, Fung, Piper, & Tennant, 1987). Given the diversity of outcomes triggered by negative life events, it may not be so unreasonable to expect that life stress could induce mania as well.…”
Section: Life Events and Maniamentioning
confidence: 99%
“…In 1884, the editor of the British Medical Journal noted that at funerals "the depression of spirits under which the chief mourners labour at these melancholy occasions peculiarly predisposes them to some of the worst effects of the chill" [1]. Since then, morbidity has been shown to be significantly increased during chronic stress in both observational [2][3][4][5] and live virus challenge [6][7][8][9] studies. These provide compelling evidence that psychological stress is associated with an impairment of the immune system's ability to respond to infection.…”
Section: Introductionmentioning
confidence: 99%